2019
DOI: 10.36478/jeasci.2020.398.409
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Organizational Culture, Organizational Trust and Self-Efficacy on Knowledge Sharing Behavior by Mediating Organizational Commitments Study on Auditors of District/City Inspectorates in East Java Province

Abstract: The role of individual's knowledge on the development of an organization demonstrates pivotal lieu for both public and private sector organizations. The needs for public sector workers who posses knowledge encourage awareness on the importance of knowledge acquisition particularly for the knowledge mastered by each of individual in the organization. Employees involved in knowledge sharing activity will boost performance and productivity. The process of knowledge sharing in an organization is driven by several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…This research was also conducted in Indonesia with several employees as respondents in Central Kalimantan Province, Indonesia. In line with a study conducted by Wahyudi et al (2020), the self-efficacy of auditors positively affects knowledge-sharing behavior in East Java Province, Indonesia. Research by Al Hawamdeh and AL-edenat (2022) also shows self-efficacy as a driver for sharing employee knowledge in public organizations in Jordan.…”
Section: Literaturesupporting
confidence: 83%
See 2 more Smart Citations
“…This research was also conducted in Indonesia with several employees as respondents in Central Kalimantan Province, Indonesia. In line with a study conducted by Wahyudi et al (2020), the self-efficacy of auditors positively affects knowledge-sharing behavior in East Java Province, Indonesia. Research by Al Hawamdeh and AL-edenat (2022) also shows self-efficacy as a driver for sharing employee knowledge in public organizations in Jordan.…”
Section: Literaturesupporting
confidence: 83%
“…This organizational commitment will raise workers' sense of duty to assist the organization in achieving its objectives, emotional commitment to the organization, and the expectation that increased performance would be appropriately rewarded (Iebra Aizpurúa et al, 2011). Research from Wahyudi et al (2020) proves that organizational commitment positively affects knowledge-sharing behavior in the East Java Province Auditors Province, Indonesia. The study of Rasdi and Tangaraja (2020) on the Malaysian public service administrator also shows that an affective organizational commitment was an intermediary factor that enables administrators with intrinsic motivation to engage in knowledge-sharing behavior.…”
Section: Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The results of a review of 26 relevant articles indicate that several important matters are discussed in more depth. In the 26 articles reviewed in this study, 13 studies measured the direct influence of organizational culture on knowledge sharing [35][36][37][38][39][40][41][42][43][44][45][46][47][48]. All these studies show the same results, namely that organizational culture has a positive and significant effect on knowledge sharing behaviour.…”
Section: Analysis and Synthesis (Discussion)mentioning
confidence: 93%
“…The influence of organizational culture on knowledge sharing can be strengthened by mediating variables. Several studies have shown an indirect effect of organizational culture on knowledge sharing through mediating variables, namely subjective norms [35], sense of well-being [10], trust [5], job autonomy [51], formal knowledge governance mechanism, knowledge-sharing opportunity [20], organizational commitment [43]; and job satisfaction [52]. Therefore, anyone who is committed to developing knowledge-sharing behaviour among organizational members, they must pay attention to subjective norms, sense of well-being, trust, formal knowledge governance mechanisms, knowledge-sharing opportunities, organizational commitment and job satisfaction of employees.…”
Section: Analysis and Synthesis (Discussion)mentioning
confidence: 99%